Benefits of Kahoot in Improving 7th Grade Junior Highschool English Vocabulary: Classroom Action Research in SMP Hamong Putera Ngaglik - Mustagis, R. Muhammad Satria Gyas; Hijayadi, Ramdani; Rufiani, Rufiani; Al Mubarok, M Teguh; Jamilah, Jamilah; Pratiwi, Dwiyani (English Education and Literature Journal (E-Jou), 2024)
This Classroom Action Research investigates the advantages of employing Kahoot, A platform that teaches through games, in expanding one's vocabulary in English among 7th grade junior high school students at SMP Hamong Putera Ngaglik. The study found that Kahoot significantly enhances student improvement, motivation, and learning outcomes. It was observed that the use of Kahoot led to an increase in vocabulary scores, indicating its effectiveness as a learning tool. The study included before being tested, Kahoot! intervention, and a vocabulary post-test. This study examined if Kahoot! could improve 7th-graders' English vocabulary acquisition and retention. The study found that Kahoot! improved pupils' vocabulary scores. Kahoot!'s gamification made learning fun and engaging. The platform's real-time feedback helped students remedy their mistakes, fostering active learning and English language comprehension. Kahoot! may help 7th-grade junior high school students learn English vocabulary, according to one study. To improve vocabulary learning, teachers can use gamification like Kahoot! This study adds to the literature on technology-enhanced learning aids in education.Keywords: Classroom Action Research, Kahoot, Vocabulary